A Study on the Athletic Age Profiles of Olympic Sprint Competitors - Nandhagopan G.; Athira B.; Aswin Prasad (Recent Trends in Sports, 2025)
This study aimed to determine the potential athletic age of male Olympic sprinters in the 100-meter event and to assess the dominance of various continents in relation to athletes' age at debut, peak performance, retirement, and competitive career span. Data were collected from the top eight finalists in the 100-meter event across Africa, Asia, Europe, North America, and South America, covering the Olympic Games from Moscow 1980 to Tokyo 2020. The selected variables included age at debut, age at peak performance, age at retirement, and competitive career span. The World Athletics (WA) database provided the data. To investigate group differences, statistical analysis was performed using one-way analysis of variance (ANOVA), with a significance level set at p < 0.05. The results indicated no statistically significant differences among sprinters from Africa, Asia, Europe, North America, and South America concerning age at debut, age at peak performance, age at retirement, and competitive career span. These results imply that the performance and career longevity of elite 100-meter sprinters across continents may be more strongly influenced by variables other than age, such as training regimens, physiological variations, and support networks. This insight emphasizes how important it is to take into account variables other than age, such as cultural and socioeconomic aspects, when assessing the athletic prowess and performance of international sprinting competitors, promoting a comprehensive approach to talent identification and development.
Keywords: Athlete Age; Performance; competitive career span; olympics; sprinters